Analisis Kinerja Komunikasi Nirkabel dalam Sistem IIoT untuk Monitoring dan Controlling pada Ruangan Oven Batang Rokok di Pabrik Indokretek Malang - Ainnur Rahayu Pratiwi; Elsa Lolita Anggraini (Politeknik Negeri Jakarta, 2026)
Temperature and humidity stability in the cigarette rod oven room is essential for maintaining drying quality and production consistency. Manual monitoring may delay the detection of changes in oven conditions, creating the need for a wireless communication-based Internet of Things (IoT) system to support real-time monitoring and control. The proposed system is developed using DHT11 sensors, Raspberry Pi 3, relay modules, LCD, Mi-Fi as a cellular gateway, Firebase, and an Android application. The experiment was conducted in an oven room measuring 216.5 cm × 194 cm. Wireless communication performance was evaluated using three parameters: delay, packet loss, and throughput under working and non-working hours. Results show an average delay of 63.89 ms during working hours and 63.50 ms during non-working hours, both below the 100 ms threshold. Average throughput was 22,291.90 bps and 6,185.12 bps for working and non-working hours, respectively, indicating sufficient capacity for periodic sensor transmission. Average packet loss was 1.06% during working hours and 0.95% during non-working hours, indicating acceptable performance, although reliability decreases slightly during working hours. Overall, the tested wireless communication system is suitable for supporting basic monitoring and control in the cigarette rod oven room.